Development of Junior High School Geometry Learning Tools Based on Computer Assisted Instruction (CAI) and Oriented to Spatial Ability - Tri Kurniah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Spatial ability is one of the important competencies in geometry learning that needs to be supported through the use of appropriate media and learning tools. This study aims to develop a geometry learning tool based on Computer Assisted Instruction (CAI) that is oriented towards improving students' spatial ability and to test its validity, practicality, and effectiveness. This research is a development research using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The products developed consist of a Lesson Implementation Plan (RPP), Student Worksheets (LKS), and CAI-based learning media. The research subjects were 101 eighth-grade students of SMP Negeri 6 Yogyakarta. Data were collected through expert validation sheets, practicality questionnaires, and spatial ability tests. The results of the study showed that all developed tools met the valid criteria based on expert assessment. The trial results also showed that the learning tools had a very good level of practicality and were effective for use in geometry learning. The effectiveness of the tools was demonstrated by the students' spatial ability completion achievement exceeding 81%. Thus, the developed CAI-based geometry learning device is suitable for use to support geometry learning and improve students' spatial abilities.